Transport Routier Et Pollution De L’air : Etude De La Conscience Environnementale Des Automobilistes Dans La Commune De Cocody (Abidjan) - Tra, Fulbert; Adou, Yedlock Marie Christiane (European Scientific Journal, ESJ, 2017)
Like other sub-Saharan African cities, Abidjan undergoes environmental and health impacts of air pollution, mainly due to the dynamism observed in recent years in the field of transport. Cocody commune of Abidjan, is a field of study relevant to the extent that the source of pollution from traffic is predominant. Both qualitative and quantitative methodology was developed to highlight significant differences between vehicle pollution and the environmental awareness of stakeholders relations. Practices of motorists do not take into account environmental concerns; they perceive the risks of automobile pollution as a necessary evil. All these elements here that reflect environmental awareness, urban air pollution explain the outcome of the traffic in Cocody.